K-W-L: A TEACHING STRATEGY TO DEVELOP STUDENTS’ READING COMPREHENSION IN THE SEVENTH GRADER OF JUNIOR HIGH SCHOOL - Khairunnisa Khairunnisa (Journal of English and Education, 2017)
This study aims to investigate the implementation of K-W-L strategy to develop seventh graders students’ reading comprehension and their involvement in the classroom activities. This study employed a mixed method design. There were two classes of seventh grade that were selected to be samples; one class of control group and one class of experimental group. Each of the class consisted of 32 students. The data were gained from the pre-test and post-test, the classroom observation, the field notes, and the interview. The results from the pre-test and post-test showed that there was a small increase of the mean of the control group whih was 11.41 (pre-test 28.75 and the post-test 40.16), meanwhile, the experimental group showed a significant increase by 46.71 (pre-test 30.16 and the post-test 75.31). In addition, the value of eta squared was 0.725, which indicated that the implementation of K-W-L strategy had large effect on students’ reading comprehension. It can be implied that the students’ reading comprehension skill could be developed through the implementation of K-W-L Strategy. The results from the classroom observation, the field notes, and the interview revealed that each step of K-W-L strategy contributed to improve reading comprehension and develop students’ involvement in the classroom activities.